ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN MAGELANG TAHUN ANGGARAN 2019-2021 - Arum Nur Aulia; Zarah Eka Nur Saputri; Risma Wira Bharata (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the financial performance of the Regional Government of Magelang Regency seen based on the Analysis of Budget Realization Reports. The Budget Realization Report is a financial report that presents an overview of the sources, allocation and use of economic resources managed by the local government. The realization report describes the comparison between the budget and its realization in one reporting period. The Budget Realization Report provides information regarding financial position that is useful for most users of the report in order to make decisions and demonstrate accountability for the use of resources entrusted to users. The method used is descriptive quantitative using the ratio of effectiveness and efficiency. Data obtained through field studies.